Selection and Identification of a DNA Aptamer for Multidrug-Resistant Acinetobacter baumannii Using an In-House Cell-SELEX Methodology - Farrel Côrtes, Marina; Marli Bes, Taniela; Ribeiro Deo, Beatriz; Barbosa dos Anjos, Beatriz; Jimenez Galisteo, Andrés; Cerdeira Sabino, Ester; Santos, Carlos; Figueiredo Costa, Silvia (Frontiers in Cellular and Infection Microbiology, 2022)
Infections caused by multidrug-resistant A. baumannii are a worldwide health concern with high mortality rates. Rapid identification of this infectious agent is critical as it can easily spread with difficult or no options for treatment. In this context, the development of reliable and economically viable detection and therapeutic methodologies are still challenging. One of the promising solutions is the development of nucleic acid aptamers capable of interacting with bacteria. These aptamers can be used for specific recognition of infectious agents as well as for blocking their functions. Cell-SELEX technology currently allows the selection and identification of aptamers and is flexible enough to target molecules present in an entire bacterial cell without their prior knowledge. However, the aptamer technology is still facing many challenges, such as the complexity of the screening process. Here, we describe the selection and identification of a new aptamer A01, using an in-house whole-cell SELEX-based methodology, against multi-resistant Acinetobacter baumannii, with rapid execution and low cost. In addition, this protocol allowed the identification of the aptamer A01 with the whole A. baumannii cell as a target. The aptamer A01 demonstrated a binding preference to A. baumannii when compared to K. pneumoniae, C. albicans, and S. aureus in fluorescence assays. Although the time-kill assay did not show an effect on bacterial growth, the potential bactericidal or bacteriostatic cannot be totally discarded. The new categorized aptamer (A01) displayed a significant binding affinity to MDR A. baumannii.